2016
DOI: 10.3390/toxins8100291
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin Exploits Host Cell Signaling Pathways Induced by Meningitis-Causing E. coli K1-RS218 and Enhances Adherence of Monocytic THP-1 Cells to Human Cerebral Endothelial Cells

Abstract: Pertussis toxin (PTx), the major virulence factor of the whooping cough-causing bacterial pathogen Bordetella pertussis, permeabilizes the blood–brain barrier (BBB) in vitro and in vivo. Breaking barriers might promote translocation of meningitis-causing bacteria across the BBB, thereby facilitating infection. PTx activates several host cell signaling pathways exploited by the neonatal meningitis-causing Escherichia coli K1-RS218 for invasion and translocation across the BBB. Here, we investigated whether PTx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…3d). PT has been shown to induce production of Cxcl2 in TY10 cerebral endothelial cells which further suggests a causal relationship between non-neutralized PT and Cxcl2 production 41 .…”
Section: Resultsmentioning
confidence: 87%
“…3d). PT has been shown to induce production of Cxcl2 in TY10 cerebral endothelial cells which further suggests a causal relationship between non-neutralized PT and Cxcl2 production 41 .…”
Section: Resultsmentioning
confidence: 87%
“…Unexpectedly, pretreatment of PTX by itself stimulated neutrophils to secrete IL-8 ( Figure 7 D). It is possible that PTX induces the secretion of IL-8 from neutrophils as it does from endothelial cells [ 32 ]. Nevertheless, the inhibitory effect of PTX on the HP-NAP-induced secretion of IL-8 by neutrophils was still significant ( Figure 7 D).…”
Section: Resultsmentioning
confidence: 99%
“…The ADP-ribosylation that is mediated by the A-protomer of PTX further inhibits the activation of Gi/o proteins by preventing them from coupling to their cognate GPCR [ 42 ]. A previous study showed that PTX by itself was able to induce the secretion of IL-8 in endothelial cells through the activation of p38-MAPK [ 32 ]. The IL-8 secretion induced by PTX could be due to its effect on the ADP-ribosylation of Gi/o-proteins or its cellular actions that are independent of ADP-ribosylation.…”
Section: Discussionmentioning
confidence: 99%